Fracture in concrete gravity dams under dynamic loading conditions. (October 2022) - Lahiri, Saptarshi Kumar; Shaw, Amit; Ramachandra, L.S.; Maity, Damodar
Abstract: Concrete gravity dams are susceptible to sudden failure under specific dynamic loading conditions such as earthquakes. In the present study, the authors explore an integrated experimental-numerical approach to identify the susceptible regions in a concrete gravity dam and characterize the localized crack patterns originating from these critical sections. A laboratory-scaled prototype dam model is prepared and tested using a Shake Table to observe the failure patterns under dynamic loading. A particle-based computational framework is employed to simulate the experimentally obtained crack patterns. The validated computational framework is then used to capture the evolution of arbitrarily evolving cracks during the seismic collapse of a concrete gravity dam.